The United Nations Convention on Contracts for the International Sale of Goods: Article 7 and uniform interpretation - Felemegas, John (2000)
The United Nations Convention on Contracts for the International Sale of Goods, 1980 ("CISG") creates a uniform law for the international sale of goods. However, textual uniformity is a necessary but insufficient step towards achieving substantive legal uniformity, since the formulation and enactment of a uniform legal text carries no guarantee of its subsequent uniform application in practice. This thesis therefore considers different approaches to the interpretation of CISG and evaluates their appropriateness for uniform international trade law, before advancing an interpretative approach based on the concept of internationality and generally acknowledged principles of commercial law, such as the UNIDROIT Principles. The analysis offered by the present writer is based on the examination of the nature, scope and function of Article 7 CISG, which expressly prescribes the direction that CISG's interpretation and application should follow and whose own interpretation will determine, to a large degree, the ultimate fate of CISG as a truly uniform code. Owing to its unique nature and limitations, it is necessary that CISG exist on top of a legal order that can provide doctrinal support and solutions to practical problems - such as gap-filling - in order to guarantee CISG's functional continuity and development without offending its values of internationality, uniformity and good faith, as expressed in Article 7(1) CISG and analysed in this thesis. It is the opinion of the present writer that CISG is, and must remain, a self-contained body of rules, independent of and distinct from the different domestic laws. Supported by analysis of the existing doctrine, as well as by case law, this thesis argues that the necessary legal backdrop for CISG's existence and application can be provided by general principles of international commercial law, such as those exemplified by the UNIDROIT Principles, which will, if adopted, render the textual reference in Article 7(2) CISG to private international law redundant - a positive step towards uniformity. The recourse to rules of private international law in the interpretation of CISG, even as a last resort, would represent regression into doctrinal fragmentation and practical uncertainty. The relevant textual reference in Article 7(2) CISG to such a method is the regrettable result of diplomatic drafting compromises and should remain inactive, since its activation would reverse the progress achieved by the world wide adoption of CISG as a uniform body of international sales law.